Understanding gender and organizations - Alvesson, Mats , 1956-; Billing, Yvonne Due (SAGE Publications, 2009)
'Understanding Gender and Organizations' provides an accessible, yet comprehensive and broadly critical overview of gender in organizations, and presents the complex and contradictory nature of gender patterns.